Temporomandibular Joint Disorders: A Pictorial Review - Salamon, Nicolas M.; Casselman, Jan W. (Seminars in Musculoskeletal Radiology, 2020)
Temporomandibular joint (TMJ) disorders are commonly encountered in the general population but often ignored or unrecognized. The detection and characterization of lesions has drastically improved over the years due to technological advances in cone beam computed tomography (CBCT) and magnetic resonance imaging (MRI). However, adequate knowledge of the normal imaging appearance on different imaging modalities as well as the broad variety of pathology is required to provide a proper radiologic assessment. This pictorial review focuses on TMJ pathology and its appearance on CBCT and MRI. A short overview of the technical aspects and normal anatomy are provided to round out this complete summary on the subject.
Keywords: temporomandibular joint; magnetic resonance imaging; cone beam computed tomography; temporomandibular joint disorders